Environmental profile of a bio-based and biodegradable foamed packaging prototype in comparison with the current benchmark. (1st September 2015) - Razza, Francesco; Degli Innocenti, Francesco; Dobon, Antonio; Aliaga, Cesar; Sanchez, Carmen; Hortal, Mercedes
Abstract: Post-consumer cushioning packaging waste made from expanded polystyrene or other conventional polymers is rarely recycled because of technical and economic constraints. Expanded packaging can also be made from renewable and biodegradable raw materials. In this case, the use of a renewable feedstock, such as starch, can reduce the oil dependence and biodegradability can enable the organic recycling of the final product. In this study, a life cycle assessment was performed on a prototype (a port-hole spacer for washing machines) developed in a research project by applying a biodegradable plastic expanded by means of microwave technology. Port-hole spacers for washing machines are mainly made from expanded polystyrene. Life cycle assessment results indicate that the prototype is characterized by a lower consumption of non-renewable energy resources (−50%) and lower greenhouse gas emissions (−60%) compared to the benchmark (expanded polystyrene packaging). This was mainly due to the use of a renewable feedstock (starch). The photochemical ozone creation potential resulted significantly lower (−90%) thanks to the abolition of the expanding agent (i.e. pentane) used in the polystyrene expansion process. The robustness of the results was assessed through data quality checks and a Monte Carlo simulation. A sensitivity analysis showed that the environmental profile of the prototype is mainly affected by the Land Use Change for global warming potential and by the type of starch used for eutrophication and acidification. The type of electricity used (i.e. fossil-based or renewable) for the microwave expansion process also affects the results. The use of biodegradable packaging makes it possible to increase the level of recovery by means of organic recycling. Considering the organic recycling rate in the countries where the washing machines are supplied it has been estimated that the cushioning packaging waste that goes to landfill would go from 52% (current scenario with expanded polystyrene packaging) to 37%, whereas recycling would go from 0.5% (mechanical recycling of expanded polystyrene) to 40% (organic recycling of the prototype). This paper shows that the use of a packaging system potentially suitable for inclusion in the industrial composting process opens new routes for waste treatment, thus increasing diversion from landfill. It can be argued that the combination of the use of renewable resources, and the possibility to get a compostable packaging product give rise to interesting future outlook. On one site a reduction of oil dependence can be achieved and, on the other side, the diffusion of packaging products not easy to recycle as post-consume waste and characterized by a very long persistence in the environment is reduced. This paper contributes to the current discussion on the benefits of bio-based and bio-degradable materials, whose production volumes are steadily increasing. Graphical abstract: Highlights: Foamed biodegradable packaging based on microwave technology was developed. Biodegradability can increase diversion from landfill of packaging. Environmental impacts of the prototype were lower than those of reference scenario. Renewable raw materials and the expansion process affect the environmental profile.